A hot-rolled composite phase 1770MPa grade wire rod for bridge cables and a manufacturing method thereof

The design of compound-phase tissue through the design of C-SI-Mn-CR components and online salt microscopic quenching has solved the problem of the existing 1770MPA bridge and cable difficulty and plastic matching difficulties, and achieved efficient production and stable performance stability , Reduce the risk of broken silk.

CN118854017BActive Publication Date: 2025-01-28JIANGSU YONGGANG GROUP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411347661.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-28
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The existing hot-rolled strips for 1770MPa-grade bridge cables have difficulties in improving strength and plastic matching, and it is difficult to take into account both production efficiency and tissue uniformity, which is prone to abnormal mesh carbon and martensite structures, resulting in large fluctuations in strength and plasticity.

Method used

Adopt C-SI-Mn-CR chemical ingredient design, combined with temperature technology such as online melting salt microscopic quenching, through temperature treatment such as fast cold speed and high temperature, forming a recovery of recovery with a genetic main body and a small amount of fire Betthion Phase organization, the strong plastic matching of the bar bars, and further optimize the organizational structure through the roller grid slowly.

Benefits of technology

The high -intensity and high plasticity of the hot rolled recovery 1770MPA -level bridge cable uses the high strength and high plasticity, which reduces performance fluctuations, takes into account high -efficiency production, reduces the risk of cold plugs, and improves the performance of bridge and cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118854017B_ABST
    Figure CN118854017B_ABST
Patent Text Reader

Abstract

The invention relates to a hot-rolled complex phase wire rod for 1770MPa-grade bridge cables and a manufacturing method thereof. After rolling and spinning into wire rods according to C-Si-Mn-Cr components, the wire rods are subjected to online molten salt micro-quenching isothermal treatment, so that the wire rods are cooled to the upper limit of the mixed phase region of pearlite and bainite at a cooling rate of ≥37°C / s to form a mixed structure composed of troostite and quenched bainite, and at the same time, the mixed structure is promoted to be isothermal tempered, and part of the troostite lamellae are melted and transformed. Finally, the wire rods are subjected to roller slow cooling to form a wire rod for bridge cables, whose microstructure includes a complex phase structure composed of mainly tempered troostite, a small amount of tempered bainite, and the rest of ferrite and melted troostite. The wire rods can realize controllable regulation and toughening of the complex phase structure of the wire rods, reach a tensile strength of 1210-1260MPa, and a cross-sectional shrinkage of 43%-48%. The wire rods are suitable for manufacturing 1770MPa-grade bridge cables, reduce the risk of wire breakage during cold drawing, and ensure the performance of bridge cables.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hot-rolled wire rods for bridge cables, and specifically relates to a hot-rolled complex phase 1770MPa grade wire rod for bridge cables and a manufacturing method thereof. Background Art

[0002] 1770MPa-grade bridge cables are commonly used cable structures for suspension bridges, cable-stayed bridges, draw bridges and other bridges. Due to the complex and changeable service conditions, the cables are easily damaged during service, causing bridge collapse. The strength, plasticity, torsion and other indicators of cold-drawn steel wire determine the performance of the cable. The better the strength, plasticity and torsion performance of the cold-drawn steel wire, the less likely the cable will be damaged during service. The cold-drawn steel wire is made of hot-rolled wire rods through wire laying, pickling, deep drawing, hot-dip galvanizing and torsion processes. Therefore, the structure and performance of the hot-rolled wire rod parent material dominate the strength, plasticity and torsion performance of the cold-drawn steel wire. Improving the uniformity of the hot-rolled wire rod parent material structure and performance indicators is an effective means to improve the performance of the final bridge cable.

[0003] Hot-rolled wire rods for 1770MPa bridge cables are usually designed with 82C basic components and CrMn alloying, and then produced into a microstructure with a high sorbite rate by the Stelmor cooling line after rolling. For example, the high-strength bridge cable and suspension cable galvanized steel wire rod and its manufacturing method disclosed in patent CN101376951B adopt C-Si-Mn-Cr-V component design, combined with high-strength wire rolling and controlled cooling by Stelmor wire fast cooling to obtain a wire rod with a sorbite content of ≥90%, achieving a tensile strength of 1170~1250MPa and a cross-sectional shrinkage of ≥30%. However, the following technical difficulties exist in manufacturing 1770MPa bridge cable wire rods with high strength and higher plasticity matching, more uniform organization and higher efficiency:

[0004] 1. The material strengthens the original strength of the wire rod by adding trace alloy elements such as Mn, Cr, and V, but it also brings about plasticity loss. In order to reduce costs and improve the plasticity of the wire rod, the alloy element content is reduced or the expensive alloy V is omitted. However, due to the limited cooling capacity of the Stelmor wire, the wire rod is incubated with troostite for a relatively short time. On the basis of maintaining production efficiency, it is difficult to obtain a troostite structure with a higher proportion and finer interlamellar spacing, which will ultimately lead to limited improvement in the plasticity of the wire rod and cause a large loss of strength, which is not conducive to reducing the risk of wire breakage by reducing the drawing reduction rate during subsequent steel wire manufacturing.

[0005] Second, since high C and Mn contents aggravate element segregation, in order to reduce the adverse effects of network carbon on the uniformity and plasticity of high carbon steel during controlled cooling, reducing the C and Mn contents will lead to a certain loss of strength. Even if Stelmor rapid cooling is adopted, the increase in wind intensity during the process will also lead to the instability of wind volume and wind direction, which will increase the temperature difference between the windward and windward sides of the wire rod, and between the overlap and non-overlap. Not only can the precipitation of network carbides along the grain boundaries still not be effectively avoided, but the fluctuation of the proportion of ferrite, troostite and network carbon in the wire rod structure will also increase. Moreover, the risk of precipitation of bainite and martensite abnormal structures in the wire rod will increase and become uncontrollable. During the continuous cooling process of Stelmor, this highly distorted brittle structure cannot be toughened at low temperature, which will easily cause the brittleness of the wire rod and increase the tendency of manufacturing cracking. It will also lead to large fluctuations in the uniformity and performance of the wire rod structure and be difficult to control. The strengthening effect of carbon is often weakened due to the uncontrollable cooling rate during the cooling phase transformation process, which will lead to an increase in the risk of wire breakage during cold drawing of the wire rod and a decrease in the performance of the bridge cable.

[0006] 3. Due to the high hardenability of the wire rod and the continuous cooling during the Stelmor controlled cooling process, in order to reduce the risk of abnormal tissue precipitation, extend the online time of the wire rod in the troostite phase zone to increase the troostite content, even if the Stelmor cooling rate is reduced or the cooling is fast first and then slow, in addition to being unfavorable for controlling the precipitation of secondary and tertiary cementite, due to the inhibitory effect of Mn on the diffusion activity of C, the effect of segregation on the fluctuation of the troostite phase transformation temperature phase zone, the effect of cementite peak precipitation on the coarsening of carbides, and the effect of reduced supercooling on the coarsening of tissue lamellae, the uniformity of the wire rod structure cannot be effectively improved, the increase in the spacing between troostite lamellae will lose a certain strength, and the softening difficulty of the wire rod structure will increase. With the end of the phase transformation, the wire rod is in a low temperature state and lacks thermal power, which further makes the residual stress and dislocation density of the final wire rod structure high, and the wire rod has insufficient plasticity, which is manifested in the high risk of drawing hardening and fracture during the wire rod drawing process. At the same time, rapid air cooling also restricts the efficient production of wire rods.

[0007] 4. Adding microalloys and low-temperature rolling can strengthen the wire rod, but it will also increase the deformation resistance of the wire, aggravate the wear of the rolling line, cause the rolling speed to drop, and the spinning temperature after rolling will drop accordingly. The segregation effect will increase the risk of carbon precipitation in the spinning stage, and it is also unfavorable for the nucleation of sorbite in the subsequent Stelmor air cooling control process. In order to improve the rolling efficiency and sorbite content, increasing the rolling and spinning temperature will bring greater pressure to the Stelmor cooling control. Slowing down the cooling rate will further extend the online time of the wire rod, making it difficult to take into account efficient production. Summary of the invention

[0008] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a hot-rolled complex phase 1770MPa grade wire rod for bridge cables and a manufacturing method thereof, which can realize the controllable regulation and toughening of the complex phase structure of the wire rod, achieve the high strength and plasticity matching of the wire rod, effectively reduce the performance fluctuation of the wire rod, and take into account efficient production. It is suitable for the manufacture of 1770MPa grade bridge cables, reduces the risk of wire breakage in cold drawing, and ensures the performance of bridge cables.

[0009] The technical solution adopted by the present invention to solve its technical problem is:

[0010] A method for manufacturing a hot-rolled complex phase 1770MPa grade wire rod for bridge cables, the manufacturing method comprising:

[0011] The wire rod is rolled and produced according to the chemical composition of the wire rod for bridge cables. The chemical composition and mass percentage of the wire rod for bridge cables include: C: 0.72%~0.76%, Si: 0.20%~0.35%, Mn: 0.7%~0.82%, Cr: 0.05%~0.15%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; the wire rod is spun into wire rod at a spinning temperature of ≥935°C, and then is subjected to online molten salt micro-quenching isothermal treatment to make the wire rod The wire rod is cooled at a cooling rate of ≥37°C / s to the upper limit of the mixed phase region of pearlite and bainite to form a mixed structure composed of troostite and quenched bainite, in which the mixed structure is mainly troostite. At the same time, the mixed structure is promoted to be isothermal tempered, and part of the troostite lamellae are melted and transformed. Finally, it is slowly cooled by a roller to form a wire rod for bridge cables with a microstructure including 82% to 88% by volume of tempered troostite, 8% to 13% by volume of tempered bainite, and the rest being a complex phase structure composed of ferrite and melted troostite.

[0012] The chemical composition and mass percentage design basis of the above-mentioned wire rod for bridge cables include:

[0013] (1) Carbon: As an economical and effective strengthening element, increasing the C content in steel is conducive to the formation of a mixed structure dominated by troostite during the online molten salt micro-quenching isothermal treatment process, increasing the volume fraction of cementite in the troostite structure and refining the cementite lamellae to play a strengthening role, ensuring the high strength characteristics of wire rods for bridge cables. However, excessive C content will lead to aggravated component segregation during the solidification process of the alloy, increase the risk of forming network cementite precipitated along the grain boundaries and producing abnormal martensite structure, and deteriorate the uniformity and toughness of the structure. Therefore, in order to improve the performance of 1770MPa bridge cables and facilitate the control of wire rod structure, the carbon content is appropriately reduced. Reducing component segregation and combining it with the online molten salt micro-quenching isothermal treatment of the wire rod after spinning can, on the one hand, comprehensively reduce the risk of secondary cementite network precipitation and destroying the uniformity of the organization, while inhibiting the peak precipitation of tertiary cementite, refining cementite carbides, and improving the utilization value of carbon, which is beneficial to the isothermal tempering of troostite and bainite. On the other hand, reducing segregation and regulating the peak precipitation temperature of troostite and bainite in the wire rod, so as to make it easier to control the proportion of tempered troostite and tempered bainite when the wire rod is in the upper limit of the mixed phase zone, and further reduce the fluctuation of mechanical properties. Therefore, the mass percentage of C is controlled to be 0.72%~0.76%.

[0014] (2) Silicon: Si is often added to steel as a deoxidizer during the smelting process. At the same time, Si dissolved in the ferrite phase will play a role in strengthening the material, inhibiting the precipitation of cementite, reducing the loss of steel wire strength, making the cementite thinner and accelerating the diffusion of carbon. It is beneficial to quickly reduce dislocations during isothermal tempering of bainite and bainite structures, thereby reducing processing time and speeding up production. However, Si is a ferrite strengthening element that can reduce the austenite phase area. Excessive silicon will increase the graphitization and decarburization tendencies of C, resulting in reduced ductility after wire drawing. Therefore, in order to take into account the high strength and toughness of wire rods for bridge cables and facilitate rapid production, the mass percentage of Si is controlled to be 0.20%~0.35%.

[0015] (3) Manganese: Mn is often added to steel as a deoxidizer during the steelmaking process. It can convert S in the molten steel into MnS to reduce hot brittleness and ensure the smooth progress of the rolling process. At the same time, manganese tends to be distributed in the cementite phase, which can expand the austenite phase region. The strength and wear resistance of the wire rod can be increased by solid solution strengthening, so that the mechanical properties of the bridge cable steel wire can be improved. However, when the Mn content is too high, it will aggravate the tendency of grain coarsening and component segregation, increase the hardenability of the wire rod, shift the C curve downward, and slow down the diffusion rate of carbon. It is not conducive to reducing the processing time of online molten salt micro-quenching isothermal treatment for rapid production and avoiding Cr precipitation coarsening. Therefore, in order to take into account the high strength and toughness of the wire rod for bridge cables and facilitate the control of the wire rod structure, the mass percentage of Mn is controlled to be 0.7%~0.82%.

[0016] (4) Chromium: Cr is a strong carbide-forming element. It can replace the iron atoms in the cementite to form alloy cementite, improve the strength of the cementite, enhance the affinity of Fe and C, improve the stability of austenite, prevent grain growth during hot rolling, and help refine the lamellar structure of the troostite structure, thereby reducing the difficulty of melting and isothermal tempering. However, Cr will increase the hardenability of the wire rod, shift the phase transformation curve to the upper left, and increase the risk of abnormal martensite structure. Excessive Cr is not conducive to material cost, plasticity, and controlling the wire rod in the pearlite and bainite mixed phase region during the online molten salt micro-quenching isothermal treatment. Therefore, in order to take into account the strength of the wire rod for bridge cables and reduce the difficulty of structure control, the mass percentage of Cr is controlled to be 0.05%~0.15%.

[0017] (5) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is ≤ 0.015%.

[0018] The above manufacturing method is based on the C-Si-Mn-Cr composition design, with a relatively low C content, no precious metal V component, and relatively lower material cost. At the same time, the C, Mn, and Cr ratios are optimized, the wire rod segregation is appropriately reduced, the wire rod hardenability is regulated, and the carbon activity is regulated by Si, which provides favorable conditions for the nucleation of sorbite, the controllable transformation of bainite, and rapid isothermal tempering, and accelerates the production rhythm. On this basis, an appropriate wire-spinning temperature is selected after the wire rod is rolled to further avoid segregation and the precipitation of secondary cementite in the wire-spinning stage caused by too low a wire-spinning temperature. At the same time, a higher wire-spinning temperature is combined with online molten salt micro-quenching isothermal treatment directly after wire-spinning:

[0019] 1. Compared with the existing Stelmor rapid cooling with a maximum cooling rate of about 10°C / s, the present invention can utilize the high heat exchange capacity of molten salt to promote extremely rapid cooling of the wire rod at a cooling rate of ≥37°C / s. Even if there is a certain segregation in the wire rod, the wire rod will skip the precipitation range of secondary cementite due to the rapid cooling, effectively avoiding the formation of network carbides at the grain boundary, and at the same time quickly inhibiting the peak precipitation of tertiary cementite at 700-800°C, avoiding the coarsening of tertiary cementite in large quantities in the crystal, thereby refining the cementite carbide and improving the uniformity of the organization, so as to improve the overall strength and plasticity of the wire rod. Rapid cooling is beneficial to efficient production.

[0020] 2. Compared with the existing Stelmor cooling phase transformation process, in which abnormal structures such as martensite are produced due to segregation and uncontrollable cooling rate, on the one hand, when the wire rod after spinning passes through the molten salt, the molten salt can wrap around the surface of the wire rod for uniform and rapid heat exchange, so the cooling rate and the same-circle temperature of the wire rod are more controllable, which can avoid the wire rod entering the martensite phase region and producing abnormal martensite structure. On the other hand, after passing through the molten salt, the wire rod can be kept consistent with the molten salt temperature for a long time of isothermal tempering treatment, rather than continuous cooling by air cooling. Therefore, the austenite structure in the wire rod after spinning can be more fully transformed into troostite and quenched bainite, avoiding insufficient transformation and residual austenite from producing martensite structure again during the subsequent roller slow cooling process, thereby effectively avoiding abnormal structure, reducing mechanical property fluctuations, and improving the strengthening effect of carbon.

[0021] 3. Compared with the existing Stelmor, which is difficult to control the organizational state due to limited cooling capacity, on the one hand, the present invention can utilize online molten salt micro-quenching isothermal treatment to quickly cool the wire rod from a higher spinning temperature to the upper limit temperature of the mixed temperature phase zone of pearlite and bainite, and can form a larger degree of supercooling to inhibit grain coarsening, which is beneficial to the formation of a mixed organization dominated by a troostite organization with fine lamellar spacing. At the same time, isothermal maintenance of this temperature upper limit can form micro-quenching, allowing a small amount of austenite to transform into a quenched bainite organization. The small amount of transformation of the bainite organization is more controllable, and the mixed organization composed of troostite as the main body and a small amount of quenched bainite is used to reduce the proportion of ferrite and provide a higher matrix strength to compensate for the strength brought by reducing carbon content and not adding V alloy. On the other hand, since the wire rod is at the upper limit temperature of the mixed phase zone, continuous cooling compared to air cooling can maintain the high temperature state of the wire rod for a longer time, which not only makes the phase change more sufficient, but also provides more thermal power, promotes the melting of some bainite lamellae to form fused bainite, and the carbide of bainite transforms to spheroidized structure to form tempered bainite, which promotes the bainite structure to reduce the dislocation density and transform into a strong and tough tempered bainite structure. The tempering state is controlled to effectively improve the plasticity of the wire rod without excessively deteriorating the strength of the wire rod. Moreover, since it only undergoes one online molten salt treatment, the process is simpler and convenient for efficient production.

[0022] Since the temperature of the wire rod is still relatively high after isothermal treatment in the upper limit of the mixed phase zone of online molten salt micro-quenching, slow cooling by rollers can further avoid the deterioration of organizational uniformity and plasticity caused by rapid cooling and the generation of local abnormal tissue in the organization. At the same time, slow cooling promotes further toughening of the wire rod organization and further melting of the troostite lamellae, thereby improving the softening effect of the wire rod and ultimately regulating the strength and plasticity matching of the wire rod.

[0023] Since the spinning temperature is relatively high, the wire rod composition is simplified and the carbon content is reduced, the heating temperature before rolling can be increased accordingly and the time in the furnace can be reduced to achieve efficient production, while avoiding the risk of burning and decarburization caused by excessive heating temperature and time in the furnace. In a preferred embodiment, before rolling, the heating temperature of the heating furnace is controlled to be ≤1130°C and the time in the furnace is ≤2.5h.

[0024] Since the spinning temperature is relatively high and the online molten salt micro-quenching isothermal treatment can refine the cementite carbide, the rolling temperature can be appropriately increased to reduce the deformation resistance of the steel billet and the load and wear on the rolling line, which is beneficial to improving the rolling efficiency. At the same time, it further promotes the homogenization of the composition, cooperates with a larger deformation amount, promotes the cumulative deformation amount of the initial rolling, and dynamic recrystallization during the final rolling process to refine the grains and further strengthen the matrix. In a preferred embodiment, during the rolling, the initial rolling temperature is controlled to be 1070~1110℃, the initial rolling reduction is 21%~31%, the final rolling temperature is ≥945℃, and the final rolling reduction is 28%~36%.

[0025] In a preferred embodiment, during the online molten salt micro-quenching isothermal treatment, the molten salt temperature is 480~515℃, and the treatment time is 250~395s. This molten salt temperature is at the upper limit of the mixed phase region of pearlite and bainite of this type of steel. If the molten salt temperature is higher and the treatment time is longer, the proportion of tempered bainite increases, the tempered bainite lamellae become coarser, the proportion of tempered bainite decreases, the strength of the wire rod decreases, and the plasticity increases. However, if the molten salt temperature is too high, it is not conducive to the formation of a small amount of quenched bainite, and the proportion of ferrite increases, which is not conducive to the strength of the matrix. On the contrary, the lower the molten salt temperature and the longer the treatment time, the proportion of tempered bainite decreases, the tempered bainite lamellae become finer, the proportion of tempered bainite increases, the strength of the wire rod increases, and the plasticity decreases. However, if the molten salt temperature is too low, the proportion of bainite formed is too large, and it is even not conducive to the formation of bainite, which will cause Larger plasticity loss increases the difficulty of softening, which is not conducive to efficient production; the longer the processing time, the more complete the transformation of the wire rod into a mixed structure composed mainly of troostite and a small amount of bainite, and the better the softening effect, the strength of the wire rod decreases and the plasticity increases, but if the processing time is too long, the wire rod will be over-softened, which is not conducive to the strength of the matrix, and even the strength and plasticity will be deteriorated due to the precipitation and coarsening of Cr, which is not conducive to efficient production; on the contrary, the shorter the processing time, the weaker the softening effect, and the plasticity of the wire rod decreases, but if the processing time is too short, the mixed structure is not fully transformed, which will increase the risk of abnormal structure or the proportion of ferrite, and is not conducive to the control of the structure proportion and structure uniformity. Therefore, the molten salt temperature and processing time can be further controlled to make the control of the complex phase structure composition and uniformity more reliable, further control the matching of the strength and plasticity of the wire rod, which is beneficial to rapid production.

[0026] Since the temperature difference between the spinning temperature and the molten salt temperature is large, a higher molten salt circulation rate is selected to increase the temperature of the molten salt at the front end of the salt bath, which can control the temperature accuracy and promote rapid cooling of the wire rod. In a preferred embodiment, during the online molten salt micro-quenching isothermal treatment, the front end molten salt circulation rate is controlled to be 550~750t / h, and the temperature rise of the molten salt at the front end of the salt bath is ≤10℃.

[0027] Since the surface and core of the wire rod are cooled down after being treated with molten salt for a period of time, the difficulty of controlling the temperature rise of the molten salt is reduced. The molten salt circulation volume can be appropriately reduced to control the temperature rise of the molten salt at the rear end of the salt bath, and precise temperature control is performed to promote the transformation of untransformed residual austenite into troostite structure, while promoting isothermal tempering of the wire rod structure. In a preferred embodiment, during the online molten salt micro-quenching isothermal treatment, the rear end molten salt circulation volume is controlled to be 150~350t / h, and the molten salt temperature rise at the rear end of the salt bath is ≤3°C.

[0028] In a preferred embodiment, the roller slow cooling adopts a control method to cool the wire rod to below 300°C at a cooling rate of 0.65-0.85°C / s for coiling. The cooling rate can be controlled to control the slow cooling softening effect and avoid the cooling rate being too slow to affect the production rhythm.

[0029] A hot-rolled complex phase 1770 MPa grade wire rod for bridge cables, wherein the wire rod for bridge cables is manufactured by any of the above-mentioned methods for manufacturing hot-rolled complex phase 1770 MPa grade wire rod for bridge cables.

[0030] The wire rod for bridge cables is designed based on the C-Si-Mn-Cr composition, which appropriately reduces the material cost. At the same time, the microstructure type is a complex phase structure composed of mainly tempered troostite, a small amount of tempered bainite, and the rest is ferrite and melted troostite. The troostite has a finer interlamellar spacing, better strength and drawing properties than pearlite, and is beneficial to rapid melting and tempering during molten salt treatment. After melting and troostite is transformed into spheroidized troostite and tempered troostite, it can retain the matrix characteristics with higher strength and further reduce the dislocation density to improve Plasticity and draw hardening problems, after a small amount of high-temperature austenite is transformed into quenched bainite and then tempered into tempered bainite, the tempered bainite can retain the high-strength characteristics of the bainite hard-brittle phase and further improve the brittleness to obtain a strengthened and toughened structure. Combined with tempered bainite to reduce the proportion of ferrite, it can make up for the strength loss caused by simplified composition, and make the formation of tempered bainite controllable. Through the organization control of the tempered state, the adverse effects of high C, Si, Cr, and bainite structure on plasticity can be effectively improved, and high strength and high plasticity matching can be achieved, which is beneficial to efficient production.

[0031] In a preferred embodiment, the tempered troostite lamella spacing is 65-115 nm, and the refined tempered troostite lamella structure has better deformation performance, which is beneficial for deep drawing wire making and ensuring high strength for bridge cables.

[0032] In a preferred embodiment, the network carbide level of the wire rod for bridge cables is level 0, which can effectively avoid the brittleness of the wire rod caused by the network carbide and improve the uniformity of the wire rod structure.

[0033] In a preferred embodiment, the mechanical property difference of the wire rod for bridge cables is ≤23MPa. Compared with the existing 1770MPa grade wire rod for bridge cables, the structure uniformity is better and the mechanical properties are well controlled, which can further reduce the risk of wire drawing and torsional cracking and improve the performance of bridge cables.

[0034] In a preferred embodiment, the wire rod for bridge cables has a smaller specification, with a diameter of 12.5~15.0mm. The tensile strength of the wire rod is equivalent to that of the prior art, while the cross-sectional shrinkage rate is significantly improved. The tensile strength is 1210~1260MPa, and the cross-sectional shrinkage rate is 43%~48%. It can be used to manufacture 1770MPa-level bridge cables and other application fields to reduce the risks of wire breakage and cracking.

[0035] Compared with the prior art, the beneficial effects of the present invention are at least:

[0036] (1) In view of the current situation that the hot-rolled wire rods for bridge cables with a 1770MPa grade are insufficient in the cooling control capacity of the production line, the risk of abnormal carbon and martensite in the wire rods is high, the wire rod structure and performance fluctuate greatly, the plasticity is insufficient, and it is difficult to take into account efficient production, the manufacturing method of the present invention adopts C-Si-Mn-Cr chemical composition design combined with online molten salt micro-quenching isothermal technology process design, after spinning, the wire rod is controlled to quickly enter the upper limit of the mixed phase region of pearlite and bainite from the high-temperature austenite state, and quickly form a mixed structure composed mainly of fine lamellar spacing troostite structure and a small amount of quenched bainite, and as the high temperature and other conditions are reached, the wire rod structure is heated to a high temperature, and the temperature is increased. Temperature treatment is carried out to promote the transformation of untransformed residual austenite into troostite structure, promote isothermal tempering of wire rod structure, melt and transform some troostite lamellae, and adjust the tempering state. Finally, it is slowly cooled by rollers to avoid plastic deterioration caused by rapid cooling, further improve the softening effect of wire rod, reduce tissue stress and dislocation density, and adjust the high strength and higher plastic matching of wire rod. The uniformity of structure is effectively improved. At the same time, the wire rod is cooled faster after online molten salt micro-quenching isothermally, and there is no need to heat treat the wire rod offline before drawing it into steel wire, which is beneficial to improving the production efficiency of wire rod and bridge cable and has good industrial applicability.

[0037] (2) In view of the current situation that the existing 1770MPa grade hot-rolled wire rod for bridge cables adopts 82C basic composition, CrMn and other elements alloying design, and the ferrite, bainite and net carbon ratio fluctuate greatly, the wire rod of the present invention is designed based on C-Si-Mn-Cr composition, which appropriately reduces the material cost. At the same time, the microstructure type is a complex phase structure composed of tempered bainite, tempered bainite, ferrite and fused bainite. The complex phase structure is mainly tempered bainite, which can effectively avoid the abnormal martensite structure and make a small amount of quenched bainite The transformation and tempering of bainite become controllable, and tempered bainite which is both strong and tough is obtained. A large amount of tempered bainite is combined with a reduced proportion of ferrite to make up for the strength loss caused by simplified composition. At the same time, high strength and high plasticity are matched through the organization regulation of the tempered state, and the tensile strength can reach 1210~1260MPa and the cross-sectional shrinkage rate can reach 43%~48%. It can be used in the manufacture of 1770MPa-level bridge cables, which can reduce the risk of wire breakage during cold drawing of wire rods and improve the performance of bridge cables, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0039] Figure 1 is a metallographic structure diagram of Example 1 of the present invention;

[0040] Figure 2 is the metallographic structure diagram of Example 2 of the present invention;

[0041] Figure 3 It is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION

[0042] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention, so as to propose the best way to implement the present invention, and are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention, but cannot be understood as any limitation on the scope of the present invention, which is limited only by the appended claims; the organization and performance testing of the wire rods obtained in the following embodiments and comparative examples include: the tensile test is carried out using "GB-T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method" to obtain tensile strength and cross-sectional shrinkage; the organization test is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, take the overlap area position as the base point, divide each circle of wire rod into 8 sections on average, take 1 tensile specimen on each section, and the strength extreme difference of the tensile specimen after the tensile test is the mechanical property same circle difference. Embodiment 1:

[0043] A preferred embodiment of the method for manufacturing the hot-rolled complex phase 1770MPa grade bridge cable wire rod of the present invention The chemical composition and mass percentage of the bridge cable wire rod include: C: 0.72%, Si: 0.35%, Mn: 0.82%, Cr: 0.05%, P: 0.013%, S: 0.014%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt micro-quenching isothermal → roller slow cooling → coiling, specifically:

[0044] The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled into plasticity, promote the homogenization of the composition, and roll the steel billet into a wire with a diameter of 14mm through a rolling line after the steel billet comes out of the heating furnace, and control the rolling speed and refine the grains with appropriate rolling temperature and reduction. Specifically: the heating temperature of the heating furnace is controlled to be ≤1125℃, the furnace time is 2.5h, the initial rolling temperature is 1100℃, the initial rolling reduction is 26%, the final rolling temperature is 975℃, and the final rolling reduction is 29%; the wire-spinning process is used to convert the wire coming out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. Through an appropriate wire-spinning temperature, the precipitation of network carbon in the wire-spinning stage is avoided, creating favorable conditions for the deformation nucleation of the fine lamellar spacing troostite phase, specifically: the wire-spinning temperature is controlled to be 950℃.

[0045] The online molten salt micro-quenching isothermal process adopts a salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the salt bath tank by a roller and quickly cooled to the molten salt temperature for online molten salt micro-quenching isothermal treatment, so that the wire rod is quickly cooled from the high-temperature austenite state to the upper limit of the mixed phase region of pearlite and bainite at a cooling rate of 37°C / s, avoiding network carbides, inhibiting the peak precipitation of tertiary cementite, refining cementite carbides, and forming a troostite structure with fine lamellar spacing as the main structure and a small amount of quenched bainite structure. The mixed structure is formed. In the subsequent high-temperature isothermal process, the temperature is precisely controlled to promote the transformation of untransformed residual austenite into sorbite structure. The mixed structure is isothermally tempered, and part of the sorbite lamellae are melted and transformed to adjust the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 515℃, the processing time is 250s, the front-end molten salt circulation volume is 550t / h, the molten salt temperature rise at the front end of the salt bath is ≤10℃, the rear-end molten salt circulation volume is 350t / h, and the molten salt temperature rise at the rear end of the salt bath is ≤3℃.

[0046] The roller slow cooling process is closed with an insulation cover, and the wire rod coming out of the salt bath tank is conveyed by rollers into the insulation cover for slow cooling treatment to avoid plastic deterioration caused by rapid cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and further melting of the sorbite layer, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to be slowly cooled to 275°C at a cooling rate of 0.85°C / s until it is coiled; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 1 As shown, the wire rod structure is 88% tempered bainite by volume, 8% tempered bainite by volume, 3% ferrite by volume, and the rest is fused bainite. The interlamellar spacing of tempered bainite is 115mm, the tensile strength is 1210MPa, the cross-sectional shrinkage is 48%, the network carbide grade is 0, and the mechanical property difference is 22MPa.

[0047] Comparative Example 1:

[0048] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 1 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → Stelmor strong air cooling → Stelmor weak air cooling, specifically: the heating temperature of the heating furnace is controlled to be ≤1050°C, the furnace time is 3h, the initial rolling temperature is 1020°C, the final rolling temperature is 880°C, and the spinning temperature is 855°C; the Stelmor strong air cooling adopts an air volume of 200,000 m per fan 3 / h, open 1~5# fans at 100%, and cool the wire rod to 640℃ at a cooling rate of 10.3℃ / s. The Stelmore weak air cooling adopts an air volume of 200,000m 3 / h, open 7~11# fans at 10%, cool the wire rod to 275℃ at a cooling rate of 2℃ / s, and obtain the finished wire rod after it comes off the line. The wire rod structure is 90% troostite and 10% ferrite by volume, the troostite lamellar spacing is 145mm, the tensile strength is 1180MPa, the cross-sectional shrinkage is 33%, the network carbide grade is 1.5, and the mechanical property same circle difference is 79MPa.

[0049] From the comparison results of Example 1 and Comparative Example 1, it can be seen that compared with the low-temperature spinning combined with the Stelmor air cooling process, it is difficult to effectively avoid the problem of network carbides, the proportions of ferrite, troostite and network carbon fluctuate greatly, resulting in large fluctuations in mechanical properties. After simplifying the composition, the tensile strength decreases, the spacing between troostite lamellae is larger, the proportion of ferrite is higher, and the dislocation density of the organization is higher, resulting in insufficient strength and plasticity. The present invention adopts C-Si-Mn-Cr chemical composition design combined with online molten salt micro-quenching isothermal technology process design, which can effectively avoid the brittleness of wire rod caused by network carbides. The microstructure type is a complex phase structure composed of tempered troostite, tempered bainite, ferrite, and fused troostite, which can effectively avoid abnormal martensitic structure, has better organizational uniformity, can achieve high strength and high plasticity matching, and is used in the manufacture of 1770MPa-level bridge cables. It can reduce the risk of wire breakage during cold drawing of wire rods and improve the performance of bridge cables.

[0050] Comparative Example 2:

[0051] A method for manufacturing a hot-rolled wire rod, which differs from Example 1 in that: the heating temperature of the heating furnace is controlled to be ≤1100°C, the furnace time is 2.8h, the initial rolling temperature is 1050°C, the final rolling temperature is 925°C, the spinning temperature is 905°C, the wire rod is cooled at a cooling rate of 32°C / s during online molten salt micro-quenching isothermal, and the finished wire rod is obtained after it comes off the line. Embodiment 2:

[0052] A preferred embodiment of the method for manufacturing the hot-rolled complex phase 1770MPa grade bridge cable wire rod of the present invention The chemical composition and mass percentage of the bridge cable wire rod include: C: 0.72%, Si: 0.33%, Mn: 0.81%, Cr: 0.09%, P: 0.015%, S: 0.012%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt micro-quenching isothermal → roller slow cooling → coiling, specifically:

[0053] The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled into plasticity, promote the homogenization of the composition, and roll the steel billet into a wire with a diameter of 15mm through a rolling line after the steel billet comes out of the heating furnace, and control the rolling speed and refine the grains with appropriate rolling temperature and reduction. Specifically: the heating temperature of the heating furnace is controlled to be ≤1130℃, the time in the furnace is 2.5h, the initial rolling temperature is 1110℃, the initial rolling reduction is 21%, the final rolling temperature is 960℃, and the final rolling reduction is 28%; the wire-spinning process is used to convert the wire coming out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. Through an appropriate wire-spinning temperature, the precipitation of network carbon in the wire-spinning stage is avoided, creating favorable conditions for the deformation nucleation of the fine lamellar spacing troostite phase, specifically: the wire-spinning temperature is controlled to be 945℃.

[0054] The online molten salt micro-quenching isothermal process adopts a salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the salt bath tank by a roller and quickly cooled to the molten salt temperature for online molten salt micro-quenching isothermal treatment, so that the wire rod is quickly cooled from the high-temperature austenite state to the upper limit of the mixed phase region of pearlite and bainite at a cooling rate of 37°C / s, avoiding network carbides, inhibiting the peak precipitation of tertiary cementite, refining cementite carbides, and forming a troostite structure with fine lamellar spacing as the main structure and a small amount of quenched bainite structure. The mixed structure is formed. In the subsequent high-temperature isothermal process, the temperature is precisely controlled to promote the transformation of untransformed residual austenite into sorbite structure. The mixed structure is isothermally tempered, and part of the sorbite lamellae are melted and transformed to adjust the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 509℃, the processing time is 295s, the front-end molten salt circulation volume is 580t / h, the molten salt temperature rise at the front end of the salt bath is ≤10℃, the rear-end molten salt circulation volume is 300t / h, and the molten salt temperature rise at the rear end of the salt bath is ≤3℃.

[0055] The roller slow cooling process is closed with an insulation cover, and the wire rod coming out of the salt bath tank is conveyed by rollers into the insulation cover for slow cooling treatment to avoid plastic deterioration caused by rapid cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and further melting of the sorbite layer, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to be slowly cooled to 280°C at a cooling rate of 0.8°C / s until it is coiled; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.

[0056] Comparative Example 3:

[0057] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which differs from that of Example 2 in that: during online molten salt micro-quenching isothermal treatment, the wire rod is cooled at a cooling rate of 39°C / s, the molten salt temperature is 475°C, and a finished wire rod is obtained after the wire rod is off the line.

[0058] Comparative Example 4:

[0059] A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that the wire rod is cooled at a cooling rate of 35°C / s during online molten salt micro-quenching isothermal treatment, the molten salt temperature is 525°C, and a finished wire rod is obtained after the wire rod is off the line. Embodiment 3:

[0060] A preferred embodiment of the method for manufacturing the hot-rolled complex phase 1770MPa grade bridge cable wire rod of the present invention The chemical composition and mass percentage of the bridge cable wire rod include: C: 0.75%, Si: 0.29%, Mn: 0.7%, Cr: 0.13%, P: 0.013%, S: 0.015%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt micro-quenching isothermal → roller slow cooling → coiling, specifically:

[0061] The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet with rollable plasticity, promote component homogenization, and roll the steel billet into a wire with a diameter of 12.5mm through a rolling line after the steel billet comes out of the heating furnace, and control the rolling speed and refine the grains with appropriate rolling temperature and reduction. Specifically: the heating temperature of the heating furnace is controlled to be ≤1110°C, the furnace time is 2h, the initial rolling temperature is 1070°C, the initial rolling reduction is 31%, the final rolling temperature is 945°C, and the final rolling reduction is 36%; the wire-spinning process is used to convert the wire coming out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. Through an appropriate wire-spinning temperature, the precipitation of network carbon in the wire-spinning stage is avoided, creating favorable conditions for the deformation nucleation of the fine lamellar spacing troostite phase, specifically: the wire-spinning temperature is controlled to be 935°C.

[0062] The online molten salt micro-quenching isothermal process adopts a salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the salt bath tank by a roller and quickly cooled to the molten salt temperature for online molten salt micro-quenching isothermal treatment, so that the wire rod is quickly cooled from the high-temperature austenite state to the upper limit of the mixed phase region of pearlite and bainite at a cooling rate of 38°C / s, avoiding network carbides, inhibiting the peak precipitation of tertiary cementite, refining cementite carbides, and forming a troostite structure with fine lamellar spacing as the main structure and a small amount of quenched bainite structure. The mixed structure is formed. In the subsequent high-temperature isothermal process, the temperature is precisely controlled to promote the transformation of untransformed residual austenite into sorbite structure. The mixed structure is isothermally tempered, and part of the sorbite lamellae are melted and transformed to adjust the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 492℃, the processing time is 348s, the front-end molten salt circulation volume is 630t / h, the molten salt temperature rise at the front end of the salt bath is ≤10℃, the rear-end molten salt circulation volume is 220t / h, and the molten salt temperature rise at the rear end of the salt bath is ≤3℃.

[0063] The roller slow cooling process is closed with an insulation cover, and the wire rod coming out of the salt bath tank is conveyed by rollers into the insulation cover for slow cooling treatment to avoid plastic deterioration caused by rapid cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and further melting of the sorbite layer, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to be slowly cooled to 268°C at a cooling rate of 0.75°C / s until it is coiled; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 3 shown.

[0064] Comparative Example 5:

[0065] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the processing time during online molten salt micro-quenching isothermal is 200 seconds, and a finished wire rod is obtained after going offline.

[0066] Comparative Example 6:

[0067] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the processing time during online molten salt micro-quenching isothermal is 550 seconds, and a finished wire rod is obtained after going offline. Embodiment 4:

[0068] A preferred embodiment of the method for manufacturing the hot-rolled complex phase 1770MPa grade bridge cable wire rod of the present invention The chemical composition and mass percentage of the bridge cable wire rod include: C: 0.76%, Si: 0.2%, Mn: 0.77%, Cr: 0.15%, P: 0.013%, S: 0.014%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt micro-quenching isothermal → roller slow cooling → coiling, specifically:

[0069] The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled into plasticity, promote component homogenization, and roll the steel billet into a wire with a diameter of 13.5mm through a rolling line after the steel billet comes out of the heating furnace. The rolling speed is increased and the grains are refined by controlling the appropriate rolling temperature and reduction. Specifically: the heating temperature of the heating furnace is controlled to be ≤1120℃, the furnace time is 2h, the initial rolling temperature is 1080℃, the initial rolling reduction is 29%, the final rolling temperature is 950℃, and the final rolling reduction is 32%; the wire-spinning process is used to convert the wire coming out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. Through an appropriate wire-spinning temperature, the precipitation of network carbon in the wire-spinning stage is avoided, creating favorable conditions for the deformation nucleation of the fine lamellar spacing troostite phase. Specifically: the wire-spinning temperature is controlled to be 940℃.

[0070] The online molten salt micro-quenching isothermal process adopts a salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the salt bath tank by a roller and quickly cooled to the molten salt temperature for online molten salt micro-quenching isothermal treatment, so that the wire rod is quickly cooled from the high-temperature austenite state to the upper limit of the mixed phase region of pearlite and bainite at a cooling rate of 39°C / s, avoiding network carbides, inhibiting the peak precipitation of tertiary cementite, refining cementite carbides, and forming a troostite structure with fine lamellar spacing as the main structure and a small amount of quenched bainite structure. The mixed structure is formed. In the subsequent high-temperature isothermal process, the temperature is precisely controlled to promote the transformation of untransformed residual austenite into sorbite structure. The mixed structure is isothermally tempered, and part of the sorbite lamellae are melted and transformed to adjust the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 480℃, the processing time is 395s, the front-end molten salt circulation volume is 750t / h, the molten salt temperature rise at the front end of the salt bath is ≤10℃, the rear-end molten salt circulation volume is 150t / h, and the molten salt temperature rise at the rear end of the salt bath is ≤3℃.

[0071] The roller slow cooling process is closed with an insulation cover, and the wire rod coming out of the salt bath tank is conveyed by rollers into the insulation cover for slow cooling treatment to avoid plastic deterioration caused by rapid cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and further melting of the sorbite lamellae, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to be slowly cooled to 285°C at a cooling rate of 0.65°C / s until it is coiled; the coiling process is used to coil the wire rod into a coil by a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage.

[0072] Comparative Example 7:

[0073] A method for manufacturing a hot-rolled wire rod, which differs from Example 4 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt micro-quenching isothermal → air cooling, specifically: the air cooling adopts a heat preservation cover to open, and the wire rod coming out of the salt bath tank is air-cooled by roller conveyor, and the wire rod is slowly cooled to 285°C at a cooling rate of 1.4°C / s, and the finished wire rod is obtained after it comes off the line.

[0074] The comparison of the metallographic structures and test results of Examples 1 to 4 and Comparative Examples 2 to 7 is shown in Table 1 below:

[0075] Table 1. Comparison of the microstructure and properties of different wire rod compositions and manufacturing methods

[0076]

[0077] It can be seen from the results of Examples 1 to 4 that the present invention is based on the C-Si-Mn-Cr composition design, which appropriately reduces the material cost, and the tensile strength is equivalent to that of the high C-Si-Mn-Cr-V wire rod in the prior art. At the same time, the cross-sectional shrinkage rate is significantly improved, and the tensile strength can reach 1210~1260MPa, and the cross-sectional shrinkage rate can reach 43%~48%. It can be used in the manufacture of 1770MPa-level bridge cables and other application fields to reduce the risks of wire breakage and cracking.

[0078] From the comparison results of Example 1 and Comparative Example 2, it can be seen that compared with lowering the spinning temperature, the rolling temperature is correspondingly lowered, which is not conducive to the nucleation of sorbite and the formation of refined lamellar spacing, and the ferrite content, the level of network carbides and the fluctuation of mechanical properties increase. After appropriately increasing the spinning temperature, a larger degree of supercooling can be formed during the online molten salt micro-quenching isothermal treatment, which avoids the precipitation of network carbides and promotes the transformation of the austenite structure into a mixed structure composed mainly of sorbite structure and a small amount of quenched bainite. The sorbite structure lamellae are finer, and the difficulty of melting and tempering softening can be reduced within the same processing time, and the strength and plasticity matching of the wire rod can be adjusted. At the same time, the spinning temperature is relatively high, and the rolling temperature can also be correspondingly increased, which is beneficial to reducing the load and wear of the rolling line and improving the rolling efficiency.

[0079] It can be seen from the results of Examples 1 to 4 that the lower the molten salt temperature and the longer the treatment time, the smaller the proportion of tempered troostite, the finer the tempered troostite lamellae, the higher the proportion of tempered bainite, the higher the strength of the wire rod and the lower the plasticity. It can be seen from the comparison results of Example 2 and Comparative Example 3 that if the molten salt temperature is too low, the cooling rate of the wire rod will increase accordingly, and the proportion of bainite formed within the same treatment time will be too large, which will cause a large plasticity loss, and increasing the difficulty of softening is not conducive to efficient production.

[0080] It can be seen from the results of Examples 1 to 4 that the higher the molten salt temperature and the longer the treatment time, the greater the proportion of tempered bainite, the coarser the tempered bainite lamellae, the lower the proportion of tempered bainite, the lower the strength of the wire rod and the higher the plasticity. It can be seen from the comparison results of Example 2 and Comparative Example 4 that if the molten salt temperature is too high, the cooling rate of the wire rod will decrease accordingly, which is not conducive to the formation of a small amount of quenched bainite within the same treatment time. The proportion of ferrite increases, which is not conducive to the strength of the matrix.

[0081] It can be seen from the results of Examples 1 to 4 that the shorter the treatment time, the weaker the softening effect and the lower the plasticity of the wire rod. It can be seen from the comparison results of Example 3 and Comparative Example 5 that the treatment time is too short, the troostite lamellae fail to melt, and the dislocation of the troostite and bainite structures is relatively high, which will lead to a significant decrease in the plasticity of the wire rod. Even if the mixed structure is not fully transformed, the risk of abnormal structure or the proportion of ferrite will increase, which is not conducive to the regulation of the structure proportion and structure uniformity.

[0082] It can be seen from the results of Examples 1 to 4 that the longer the treatment time, the more complete the transformation of the wire rod into a mixed structure composed mainly of troostite and a small amount of bainite, and the better the softening effect, the wire rod strength decreases and the plasticity increases. It can be seen from the comparison results of Example 3 and Comparative Example 6 that too long a treatment time will cause the wire rod to be excessively softened, which is detrimental to the strength of the matrix and even deteriorate the strength-plasticity properties due to the precipitation and coarsening of Cr.

[0083] From the comparison results of Example 4 and Comparative Example 7, it can be seen that compared with air cooling, slow roller cooling can further avoid the deterioration of organizational uniformity and plasticity caused by rapid cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and further melting of the troostite lamellae, thereby improving the softening effect of the wire rod.

[0084] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention, and they are not intended to limit the protection scope of the present invention. For example: the steel billet is obtained by sequentially undergoing converter smelting, refining, and continuous casting processes; a group of circulation pipelines and temperature detectors are arranged at the front end of the salt bath tank to control the front end molten salt circulation amount and the front end molten salt temperature rise, and another group of circulation pipelines and temperature detectors are arranged before and after the salt bath tank to control the rear end molten salt circulation amount and the rear end molten salt temperature rise. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for manufacturing a hot-rolled complex phase 1770MPa grade wire rod for bridge cables, characterized in that: The manufacturing method thereof comprises: The wire rod is rolled and produced according to the chemical composition of the wire rod for bridge cables, and the chemical composition and mass percentage of the wire rod for bridge cables include: C: 0.72%~0.76%, Si: 0.20%~0.35%, Mn: 0.7%~0.82%, Cr: 0.05%~0.15%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥935°C, it is subjected to an online molten salt micro-quenching isothermal treatment, so that the wire rod is cooled at a cooling rate of ≥37°C / s to a mixed state of pearlite and bainite. The upper limit of the phase combination zone is formed to form a mixed structure composed of troostite and quenched bainite, the mixed structure is mainly troostite structure, and at the same time, the mixed structure is promoted to be isothermal tempered, and part of the troostite lamellae are melted and transformed, and finally, it is slowly cooled by a roller to be made into a wire rod for bridge cables with a microstructure including 82% to 88% by volume of tempered troostite, 8% to 13% by volume of tempered bainite, and the rest being ferrite and melted troostite. During the online molten salt micro-quenching isothermal treatment, the molten salt temperature is 480 to 515°C, and the treatment time is 250 to 395s.

2. The method for manufacturing the hot-rolled multi-phase 1770 MPa grade bridge cable wire rod according to claim 1, characterized in that: Before the rolling, the heating temperature of the heating furnace is controlled to be ≤1130°C and the time in the furnace is controlled to be ≤2.5h.

3. The method for manufacturing the hot-rolled complex phase 1770 MPa grade bridge cable wire rod according to claim 1, characterized in that: During the rolling, the initial rolling temperature is controlled to be 1070-1110° C., the initial rolling reduction is 21%-31%, the final rolling temperature is ≥945° C., and the final rolling reduction is 28%-36%.

4. The method for manufacturing the hot-rolled complex phase 1770 MPa grade bridge cable wire rod according to claim 1, characterized in that: During the online molten salt micro-quenching isothermal treatment, the front-end molten salt circulation rate is controlled to be 550-750 t / h, and the temperature rise of the molten salt at the front end of the salt bath tank is ≤10°C.

5. The method for manufacturing the hot-rolled complex phase 1770 MPa grade bridge cable wire rod according to claim 1, characterized in that: During the online molten salt micro-quenching isothermal treatment, the rear end molten salt circulation rate is controlled to be 150-350 t / h, and the temperature rise of the molten salt at the rear end of the salt bath tank is ≤3°C.

6. The method for manufacturing the hot-rolled complex phase 1770 MPa grade bridge cable wire rod according to claim 1, characterized in that: The roller slow cooling adopts the method of controlling the wire rod to cool to below 300°C at a cooling rate of 0.65-0.85°C / s for coiling.

7. A hot-rolled complex phase 1770MPa grade wire rod for bridge cables, characterized in that: The wire rod for bridge cables is manufactured by the method for manufacturing hot-rolled complex phase 1770 MPa grade wire rod for bridge cables as described in any one of claims 1 to 6.

8. The hot-rolled multi-phase 1770 MPa grade wire rod for bridge cables according to claim 7, characterized in that: The interlamellar spacing of the tempered bainite is 65-115 nm, the network carbide grade of the wire rod for bridge cables is grade 0, and the mechanical property difference is ≤23 MPa.

9. The hot-rolled multi-phase 1770 MPa grade wire rod for bridge cables according to claim 7, characterized in that: The wire rod for the bridge cable has a diameter of 12.5-15.0 mm, a tensile strength of 1210-1260 MPa, and a cross-sectional shrinkage rate of 43%-48%.

Citation Information

Patent Citations

  • High strength wire rod for bridge stay cable and suspended cable galvanized steel wire, and manufacturing method thereof

    CN101376951B

  • Ferrite and pearlite structure SWRH72BCr-1 prestressed hot-rolled wire rod and preparation method thereof

    CN117448680A

  • 14.9-grade annealing-free hot-rolled high-carbon cold heading steel wire rod and manufacturing method thereof

    CN118621230A